Understanding the factors influencing quality of writing and wiping for chalk and board system - Thakur, Rajendra S.; Shukla, Jignesh J.; Desale, Girish R.; Ghosh, Pushpito K. (Current Science, 2017)
This article reports the properties of a calcium carbonate-based writing chalk prepared at the CSIR-Central Salt and Marine Chemicals Research Institute (CSIR-CSMCRI) and, further, our efforts to understand the process of writing with the chalk on two different boards. The optimum density of the chalk was found to be 1.52 g ml(-1), keeping in mind the careful balancing act between strength and dust-free nature of the chalk on one hand, and the ease of particle transfer onto the board on the other. Writing with the chalk yielded thin and compact appearance on a ceramic board, while that on a polymeric board was relatively broad and dispersed. Atomic force and scanning electron microscopic studies were carried out to rationalize the observation by correlating roughness on the board with the distribution of chalk particles. Wiping efficiency of the polyurethane-based duster prepared at CSIR-CSMCRI was compared with commercial duster, and the observations rationalized again with the scanning electron microscopy.